Povyshenie effektivnosti dvizhenii v przhkakh v dlinu na osnove icpol'zovaniya sovremennykh informatsionnykh tekhnologii - Shulgaty, L. P.; Shpitalny, V. B.; Formichenko, N. G. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The use of modern information technologies in training and competition opens new possibilities for the calculation of movements efficiency. The run up has especially been studied . It has been shown that only a running velocity of 93 to 95 % of maximum in the run up leads to optimal results.